2(3y-6)=

Simple and best practice solution for 2(3y-6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3y-6)= equation:


Simplifying
2(3y + -6) = 0

Reorder the terms:
2(-6 + 3y) = 0
(-6 * 2 + 3y * 2) = 0
(-12 + 6y) = 0

Solving
-12 + 6y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 6y = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 6y = 0 + 12
6y = 0 + 12

Combine like terms: 0 + 12 = 12
6y = 12

Divide each side by '6'.
y = 2

Simplifying
y = 2

See similar equations:

| 8x+3y=101 | | -4(8+5x)=-32 | | 14=4a+2 | | 5x+11=7-2x | | -94=-2(5m+7) | | -2(7x-5)+3=-14x+13 | | p/7=6.8.k/4=2 | | 3x+11=12+8x | | 193=-x+96 | | -9x-13=50 | | 60x-3x^/3x | | 7(2x+2)=-84 | | 6x-8=6(x-5) | | 23=8*1+y | | 6460-h=4181 | | 1/4=b=3.4 | | 4.6d=26.68 | | 16x-6x=56 | | 10x+7=3x+15 | | 2/3(6x-12)=-16 | | 2/3(6x-12)=- | | 440=(11)(x)(x-3) | | 92.99=x+.89 | | X+5=4.3 | | 1/2-1/14 | | -5+55=33x+21 | | 4(4.3+-1y)+y=2.2 | | 4/3=-6e-5/4 | | 4+3(4k-5)=85 | | 252=88-x | | 6k+1=7 | | x+1=-3-(-2) |

Equations solver categories